A comparison of once and twice daily administration of trilostane to dogs with hyperadrenocorticism - Augusto, M.; Burden, A.; Neiger, R.; Ramsey, I. (Tierärztliche Praxis Ausgabe K: Kleintiere / Heimtiere, 2012)
Objective: This retrospective study describes the use of trilostane given once versus twice daily in dogs with hyperadrenocorticism (SID vs. BIDgroup) in separate clinical trials.Material and methods: The groups were compared over a six month period using laboratory findings, dose required to suppress post-ACTH cortisol, and clinical scores from owner and clinician questionnaires.Results: Ninety-three dogs enrolled the trials but for analysis of the final visit results only 56 dogs filled the inclusion criteria: 30 dogs in the SID-group and 26 dogs in the BID-group. Both treatment groups showed an improvement in clinical scores with time and no significant difference between them. In the BID-group post-ACTH cortisol concentrations went below 250 nmol/l sooner and in a higher proportion of dogs than in the SID-group.Twice-daily administration of trilostane also achieved a faster and more effective control for comparable daily doses. A higher individual tolerability (based on clinical scores) was found in the SID-group but there were no supporting laboratory findings. No dogs developed serious side-effects.Conclusion: This study reveals only small practical differences between once and twice daily trilostane administrations in treating hyperadrenocorticism. And the overall benefits of twice daily dosing have to be considered against the effect on the owners and their compliance with treatment.
Keywords: Hyperadrenocorticism; dogs; trilostane treatment